Quanten und die Wirklichkeit des Geistes: Eine Untersuchung zum Leib-Seele-Problem - Krüger, Ralf (transcript, 2015)
Are the thoughts that a person thinks just as real as the neurons in their brain? The contemporary theories of neuroscience and neurobiology don't allow for any representation of the psyche, consciousness or even thoughts within the world as it can be known by the natural sciences. Ralf Krüger confronts this blind spot with a »protyposis concept of quantum information« by Thomas and Brigitte Goernitz – an expansion of the »ur-theory« which traces back to Carl Friedrich v. Weizsäcker. Departing from the thesis that thoughts are quantum data, connections to Gestalt psychology, to Karl Popper's »World 3«, and importantly, to practical medicine, can be illustrated.